Managing cloud native applications - Garrison, Justin; Nova, Kris (O'Reilly, 2018)
What you'll learn and how you can apply it:Cloud native applications are designed to be maintained by infrastructure. This lesson will offer best practices for designing resilient, simple solutions and give you some starting points for making your applications run smoothly on cloud native infrastructure. This lesson is for you because you are a cloud engineer who wants to learn best practices for making applications run smoothly on cloud native infrastructure.